Kidney diseases: definitions, diagnosis and approaches to prevention and treatment. Module 2 - Berezin, A. E.; Vizir, V.; Demidenko, O.; Березін, Олександр Євгенійович; Візір, Вадим Анатолійович; Деміденко, Олександр Вікторович (Запорізький державний медичний університет, 2019)
The executive task force is provided to the students of medical institutions of higher education for self-education on some topics in the fields of nephrology incorporatied onto discipline of «Internal Medicine». There is information about most important topics regarding diagnosis of renal diseases.